Aspectos jurídicos da reprodução assistida - Marrey, José Guilherme Di Rienzo (2010)
Assisted human reproduction that, on one hand, has promoted a huge advance in the field of Reproductive Medicine, on the other hand, has conveyed countless polemic questions, both in the ethical and juridical spheres, as for instance, the donation of gametes and the destination for exceeding embryos. The present work seeks to analyze some foreign legislation about assisted human reproduction, as well as the bills in process in Brazil, expounding afterwards the opinion of doctrine experts